Determination of the biosphere compatible environment attractors of urbanized territories at the organization of modern construction development - Chernyshev, Denys; Predun, Konstantyn; Ivakhnenko, Iryna; Druzhynin, Maxim; Ruchinskaya, Julia (КНУБА, 2018)
The article considers current trends in ecological construction based on the principles of biosphere compatibility. The necessity of an integrated, multi-level approach to addressing the environmental safety of urbanized areas and the renovation of the urban environment is shown. The evolution of ecological-economic systems in the organization of biosphere-compatible construction can be interpreted as a sequential transition of the system from one attractor to the second through unstable chaotic states and sharp break points (bifurcation points). The article considers the issues of defining and specifying properties, conditions, evolution of ecological-economic systems as an object of management from the level of the national economy to an investment project. Generalized indicators of the biosphere compatibility of territories and the level of implementation of city functions are proposed, a method for calculating the components of the humanitarian balance is developed on the basis of a comprehensive analysis and the accepted concept of improving the environmental safety of construction sites. Further, the presented algorithm enables monitoring to form a phase portrait of an attractor of ecological-economic systems based on an assessment of biosphere compatibility indicators.
Keywords: ecological construction; biosphere compatibility; construction development; attractor; ecological-economic system; the department water supply and sewage systems; the department heat and gas supply and ventilation; the department construction manegment; 69.05:699.8; 711.4:504